Fishery-independent surface abundance and density estimates of swordfish (Xiphias gladius) from aerial surveys in the Central Mediterranean Sea. (July 2017) - Lauriano, Giancarlo; Pierantonio, Nino; Kell, Laurence; Cañadas, Ana; Donovan, Gregory; Panigada, Simone
Abstract: Fishery–independent surface density and abundance estimates for the swordfish were obtained through aerial surveys carried out over a large portion of the Central Mediterranean, implementing distance sampling methodologies. Both design- and model-based abundance and density showed an uneven occurrence of the species throughout the study area, with clusters of higher density occurring near converging fronts, strong thermoclines and/or underwater features. The surface abundance was estimated for the Pelagos Sanctuary for Mediterranean Marine Mammals in the summer of 2009 (n=1152; 95%CI=669.0–1981.0; %CV=27.64), the Sea of Sardinia, the Pelagos Sanctuary and the Central Tyrrhenian Sea for the summer of 2010 (n=3401; 95%CI=2067.0–5596.0; %CV=25.51), and for the Southern Tyrrhenian Sea during the winter months of 2010–2011 ( n=1228; 95%CI=578–2605; %CV=38.59). The Mediterranean swordfish stock deserves special attention in light of the heavy fishing pressures. Furthermore, the unreliability of fishery–related data has, to date, hampered our ability to effectively inform long-term conservation in the Mediterranean Region. Considering that the European countries have committed to protect the resources and all the marine-related economic and social dynamics upon which they depend, the information presented here constitute useful data towards the international legal requirements under the Marine Strategy Framework Directory, the Common Fisheries Policy, the Habitats and Species Directive and the Directive on Maritime Spatial Planning, among the others.